2011
DOI: 10.1177/1545968311410942
|View full text |Cite
|
Sign up to set email alerts
|

Neurological Principles and Rehabilitation of Action Disorders

Abstract: This third paper discusses the evidence for the rehabilitation of the most common movement disorders of the upper extremity. We also present a framework, building on the CAP model, for incorporating some of the principles discussed in the two previous papers by Frey et al. and Sathian et al. in the practice of rehabilitation, and for discussing potentially helpful interventions based on emergent neuroscience principles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 19 publications
1
97
0
1
Order By: Relevance
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…666,728,729,[731][732][733] A variety of interventions have been the focus of ≥1 studies but have not yet been shown to be consistently beneficial for upper limb motor rehabilitation. These include somatosensory stimulation [734][735][736][737][738] and noninvasive brain stimulation (transcranial magnetic stimulation or tDCS) in combination with upper extremity exercise therapy, [739][740][741][742][743][744][745][746] interventions targeting motor apraxia, 458 and manual therapy approaches such as stretching, passive exercise, and mobilization, 748 although these approaches are a routine part of practice for individuals with more severely affected upper extremities to prevent contractures and to manage spasticity.…”
Section: Iib Bmentioning
confidence: 99%
“…The current data suggest that resolving edema and resolution/ attenuation of inflammatory responses drive the normalization of perilesional T 2 values in L-655,708-treated animals. 38 In addition to the progressive reduction in necrotic core and perilesional tissue volume, L-655,708 treatment elicited skilled reaching ability improvement. Importantly, sensorimotor improvement on the Montoya staircase test is rare because of the specificity and difficulty of the task, underscoring the significance of the present observation of recovery to~62% of baseline reaching ability after 2 weeks of treatment.…”
Section: ) (A)mentioning
confidence: 99%
“…4,5 The rationale was that AO primed brain regions involved in movement production, enhancing the benefits of subsequent movement practice. 6 Results in stroke were encouraging, 4,7,8 but few studies have assessed AO therapy in children with CP. Buccino et al 9 undertook a pilot study of 15 children aged 6 to 11 years with hemiplegia or tetraplegia.…”
mentioning
confidence: 99%